ANALISIS KOMPARATIF KEBIJAKAN OPERASIONAL RUANG DIAGNOSTIK INVASIF DAN INTERVENSI NONBEDAH RS. TK. II MOH. RIDWAN MEURAKSA JAKARTA TIMUR - Rosita, Sarwi Astuti Prapto; Arini, Nining; Hendarwan, Harimat (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Cardiovascular technical service standards are guidelines followed by cardiovascular technicians in providing health services to clients in the form of examination techniques for cardiovascular abnormalities using vascular sonography techniques, echocardiographic sonographic techniques, electrocardiography and blood pressure techniques, and cardiac catheterization techniques. The purpose of this study was to analyze the suitability of operational policies for invasive diagnostic rooms and non-surgical interventions with Law no. 36 of 2009 and also explained in the Regulation of the Minister of Health of the Republic of Indonesia No. 91 of 2014 and No. 10 of 2015 Appendix VII as the development of cardiac installations in hospitals. kindergarten. II Moh. Ridwan Meuraksa. This research method uses a comparative descriptive method with a qualitative approach in which the researcher describes the operational policies of the invasive diagnostic room and non-surgical interventions with related policies. The results of the study were obtained based on the results of observations and interviews. . Tk II Moh. Ridwan Meuraksa, referring to what is also contained in the Regulation of the Minister of Health of the Republic of Indonesia Number 91 of 2014 and Permenkes Number 10 of 2015 attachment VIII, obtained conformity to the standard of cardiovascular technical services in invasive diagnostic rooms and non-surgical interventions based on SOPs in hospitals. Tk II Moh. Ridwan Meuraksa according to Permenkes No. 91 of 2014 it was found that 81.8% of the equipment was in accordance with applicable standards in cathlab action services. It can be suggested as input material in determining standards of conformity of cardiovascular engineering service standards in invasive diagnostic rooms and non-surgical interventions to improve the standard of equipment and completeness of cathlab services in improving better servicess